Syncretism in Rasolan Tradition among Nahdlatul Ulama Madurese Society - Ellisa M Sholeh (Lakpesdam PCNU Kota Salatiga, 2021)
Madura has a variety of cultures, traditions and customs not widely known by the younger generation. Culture and traditions believed hereditary and constitute the identity of the nation must be maintained and conversed by the nation's successor. One of them is Rasolan tradition in Sumber Jerangoh hill, Mandala Village, Rubaru District, Sumenep Regency, Madura Island. Until now, this tradition is still being carried out as a form of gratitude to the one God and Islamic brotherhood because this tradition has made harmony in the life of social structure, especially in Mandala Village. The society of Mandala Village remains enthusiastic in carrying out the Rasolan procession amid the influence of modern culture which has begun to change the mindset of the society of Mandala Village towards culture. Cultures and traditions need to be published widely to society in various ways to conserve regional culture. The Rasolan tradition carried out by the society of Mandala Village, Rubaru district, Sumenep Regency, Madura Island is an annual tradition as a legacy from ancestors. The Rasolan tradition carried out on the hill named